The The Association Between Diet Satisfaction and Hospital Length of Stay in Ischaemic Stroke Patients at National Brain Centre Hospital Prof.Dr.dr Mahar Mardjono Jakarta - Silviani, Fatma; Utari, Diah Mulyawati; Rodlia; Permatasari, Zulaikhah Atyas (UHAMKA PRESS, 2022)
Ischaemic stroke patients tend to be malnourished. Diet satisfaction based on food waste can be used to evaluate food intake in hospitalized patients. A previous study found that there was a correlation between food waste and hospital length of stay. The aim of the study was to explore the association between diet satisfaction and hospital length of stay in ischaemic stroke patients at National Brain Centre Hospital Prof.Dr.dr Mahar Mardjono Jakarta. Design of the study was cohort retrospective. The study recruited 103 ischaemic stroke patients aged from 18 to 59 years old. Data was analysed by using chi-square test. The percentage of ischaemic stroke patients who had prolonged length-of-stay or >5 days was 34%. The proportion of low food waste was higher in patients who stayed at hospital ≤5 days (70%) than >5 days (30%). It may conclude that most patients with a short-hospitalized length of stay had low food waste. High food waste was a risk factor for hospital length of stay (RR=1.59, CI: 0.927-2.742), but the correlation between diet satisfaction based on food waste and hospital length of stay was not significant (p=0.112).